2022
DOI: 10.2174/1567205020666221227090125
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbiome and Alzheimer’s Disease: A Growing Relationship

Abstract: Evidence that the gut microbiota plays a key role in the pathogenesis of Alzheimer’s disease is already un-ravelling. The microbiota-gut-brain axis is a bidirectional communication system that is not fully understood but includes neural, immune, endocrine, and metabolic pathways. The progression of Alzheimer’s disease is supported by mechanisms related to the imbalance in the gut microbiota and the development of amyloid plaques in the brain, which are at the origin of Alzheimer's disease. Alterations in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 113 publications
0
4
0
1
Order By: Relevance
“…The development of Alzheimer’s disease [ 69 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ] and the mechanisms through which the microbiome can contribute to the progression of Alzheimer’s disease have been investigated [ 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 ]. Numerous studies are also available regarding treatments with probiotics […”
Section: Discussionmentioning
confidence: 99%
“…The development of Alzheimer’s disease [ 69 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ] and the mechanisms through which the microbiome can contribute to the progression of Alzheimer’s disease have been investigated [ 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 ]. Numerous studies are also available regarding treatments with probiotics […”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is intriguing that OMVs of different bacteria were proposed as possible factors involved in the development of Alzheimer's disease and other neurodegenerative disorders [57,58]. Moreover, it was suggested that bacterial amyloid-like proteins may stimulate human/animal β-amyloid accumulation by mechanisms involving the cross-seeding of misfolded proteins due to molecular mimicry [59]. Since Hfq contains the amyloid-like domain, one could speculate that its inclusion in OMVs produced by gut bacteria, like E. coli, might be an especially important risk factor for stimulating the development of neurodegenerative diseases in animals and humans.…”
Section: Discussionmentioning
confidence: 99%
“…Die kausale Therapie zielt auf die Elimination des pathologischen Plasmazellklons ab und liegt, bedingt durch die komplexen neueren Therapieschemata, meist in den Händen der Hämatoonkologie 25 . Die teils ausgeprägte Proteinurie ist therapeutisch nur schwer zu beeinflussen.…”
Section: Leichtkettenamyloidoseunclassified